Coexistence of benign phyllodes tumor and invasive ductal carcinoma in distinct breasts: case report - Barbalaco Neto, Guerino; Rossetti, Claudia; Souza, Natalia A.; Fonseca, Fernando L. A.; Azzalis, Ligia Ajaime; Campos Junqueira, Virginia Berlanga; Valenti, Vitor Engrácia [UNESP]; Abreu, Luiz Carlos de [UNESP] (Biomed Central Ltd., 2012)
This report describes a rare case of coexistence of benign phyllodes tumor, which measured 9 cm in the right breast, and invasive ductal carcinoma of 6 cm in the left breast, synchronous and independent, in a 66-year-old patient. The patient underwent a bilateral mastectomy due to the size of both lesions. Such situations are rare and usually refer to the occurrence of ductal or lobular carcinoma in situ when associated with malignant phyllodes tumors, and more often in ipsilateral breast or intra-lesional.
Keywords: Breast; Phyllodes tumor; Carcinoma